2017
DOI: 10.5194/amt-10-2759-2017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and attribution of OCO-2 XCO<sub>2</sub> uncertainties

Abstract: Abstract. Evaluating and attributing uncertainties in total column atmospheric CO 2 measurements (XCO 2 ) from the OCO-2 instrument is critical for testing hypotheses related to the underlying processes controlling XCO 2 and for developing quality flags needed to choose those measurements that are usable for carbon cycle science.Here we test the reported uncertainties of version 7 OCO-2 XCO 2 measurements by examining variations of the XCO 2 measurements and their calculated uncertainties within small regions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(74 citation statements)
references
References 21 publications
5
68
1
Order By: Relevance
“…For GOSAT, standard deviations (SDs) of 1.7 ppm were found vs. TCCON measurements with 0.5-0.8 ppm of that error irreducible by averaging, implying a bias of that order (Kulawik et al, 2016). For OCO-2 typical land measurements are found to have a precision and accuracy of approximately 0.75 and 0.65 ppm, respectively, based on the small region consistency assumption, which may well underestimate the bias between regions (Worden et al, 2017). A substantial portion of this error is likely related to interferences such as aerosols or surface albedo.…”
Section: J B Abshire Et Al: Airborne Co 2 Ipda Lidarmentioning
confidence: 94%
“…For GOSAT, standard deviations (SDs) of 1.7 ppm were found vs. TCCON measurements with 0.5-0.8 ppm of that error irreducible by averaging, implying a bias of that order (Kulawik et al, 2016). For OCO-2 typical land measurements are found to have a precision and accuracy of approximately 0.75 and 0.65 ppm, respectively, based on the small region consistency assumption, which may well underestimate the bias between regions (Worden et al, 2017). A substantial portion of this error is likely related to interferences such as aerosols or surface albedo.…”
Section: J B Abshire Et Al: Airborne Co 2 Ipda Lidarmentioning
confidence: 94%
“…It is in a Sun‐synchronous orbit and has an equatorial crossing time of around 1 P.M. local solar time. Worden et al [] found typical land measurement precision (1 σ ) and accuracy to be 0.75 ppm and 0.65 ppm with the caveat that the precision estimate includes effects of synoptic variability. We describe the filtering of OCO‐2 data and “background” selection in Appendix .…”
Section: Data Setsmentioning
confidence: 99%
“…The standard deviation of the observations is used to approximate the model representation errors. The mean of the observation error statistics within the 1° × 1° box are used to represent biases, assuming biases are dominant relative to random errors (88).…”
Section: Oco-2 Xco2 Observationsmentioning
confidence: 99%